2020
DOI: 10.16965/ijar.2020.163
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Sociodemographic Characteristics and Prepregnancy Biometric Indices With Birth Weight Outcome Among Ghanaian Women in the Kumasi Metropolis

Abstract: Background:Maternal sociodemographic characteristics affect birth weight, an important predictor of neonatal morbidity and mortality. Maternal lipid levels during pregnancy have been linked to abnormal birth weight. Notwithstanding, there is lack of data on the maternal sociodemographic characteristics and early maternal lipid levels on birth weight outcomes in Ghana. This study therefore sought to determine the relationship between maternal sociodemographic characteristics,early maternal lipid levels and birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…These present ndings are in line with study ndings reported in Nigeria between the Delta Igbos and Isokos where statistical signi cance were observed in the mean left and right hand breadths as well as the mean left hand lengths of both ethnic groups [10]. People from savanna zone of Ghana are noted for their physical activities, culture and lifestyle [21], which could explain the high hand dimensions observed for Northerners. The present ndings also, contradict study report which found no statistical signi cance difference in hand dimensions when ve ethnic groups were studied [16].…”
Section: Discussionsupporting
confidence: 92%
“…These present ndings are in line with study ndings reported in Nigeria between the Delta Igbos and Isokos where statistical signi cance were observed in the mean left and right hand breadths as well as the mean left hand lengths of both ethnic groups [10]. People from savanna zone of Ghana are noted for their physical activities, culture and lifestyle [21], which could explain the high hand dimensions observed for Northerners. The present ndings also, contradict study report which found no statistical signi cance difference in hand dimensions when ve ethnic groups were studied [16].…”
Section: Discussionsupporting
confidence: 92%
“…These present ndings are in line with study ndings reported in Nigeria between the Delta Igbos and Isokos where statistical signi cance were observed in the mean left and right hand breadths as well as the mean left hand lengths of both ethnic groups (Igbigbi et al, 2018). People from savanna zone of Ghana are noted for their physical activities, culture and lifestyle (Bimpong, et al, 2020), which could explain the high hand dimensions observed for Northerners. The present ndings also, contradict study report which found no statistical signi cance difference in hand dimensions when ve ethnic groups were studied (Hasanur et al, 2023).…”
Section: Discussionsupporting
confidence: 92%